IMPROVING READING COMPREHENSION IN NARRATIVE TEXT THROUGH READ, IMAGINE, DESCRIBE, THE EVALUATE AND REPEAT (RIDER) STRATEGY OF ELEVENTH GRADERS OF SMA N 1 JARAI: CLASSROOM ACTION RESEARCH - M Bambang Purwanto (Journal of English Education, Literature and Linguistics, 2021)
This study is a classroom action research that aims at improving students’ reading comprehension achievement in the narrative text through the RIDER strategy. The subject of this study were 28 students of XI. IPA 3 of Senior High School 1 of Jarai in the academic year 2015/2016. The research was conducted in two cycles (1 and 2 ) and the preliminary stage was initiated before the study was done. Each cycle has four steps; (1) Planning ; (2) Action ; (3) Observation, and (4) Reflection. The last step of each cycle was administered to what to do to the next cycle. There are two data collections, namely quantitative and qualitative. Tests are used as quantitative and observation is quantitative data. The mean and percentage are used to score the tests. Meanwhile, the qualitative data are interpreted by describing the result of the observation form. The findings show that there are improvements in students’ reading comprehension achievement in narrative text. From the mean score of students’ reading test, the achievements score are 70.17 for cycle 1; 78.57 for cycle 2. The improvements of the study for reading tests are 60.01% in cycle 1, 50 % for cycle 2. The result of observation also shows the improvement of students’ motivation in learning text. The observation is divided into two categories; active students and inactive students. In cycle 1, there were 11 students or 39.28 % for inactive students, in cycle 2 there were 4 or 14.28 % inactive students. Meanwhile, in cycle 1 there were 17 or 60.71% active students, and 24 or 85.71 % active students for cycle 2, From these data, therefore, the implementation of the RIDER ( Read, Imagine, Describe, Evaluate and Repeat ) strategy is appropriate strategy to improve students’ reading comprehension achievement in narrative text. And the criteria of success have been reached successfully.